2021
DOI: 10.1017/s1047951121004881
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo syndrome as a cardiac manifestation of multisystem inflammatory syndrome in children

Abstract: Cases of severe heart damage in patients presenting with multisystem inflammatory syndrome in children are one of the most intriguing phenomena during the coronavirus disease of 2019 pandemic. The pathophysiology of myocardial changes in the course of this syndrome has not been fully understood yet. We present a case of a child with multisystem inflammatory syndrome in children and with cardiac changes corresponding to Takotsubo syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
1
8
1
Order By: Relevance
“…Such a strong inflammatory reaction can be seen as a sufficient trigger for the occurrence of TTS. Belhadjer mentioned an echocardiographic image resembling TTS in a patient with acute heart failure in the course of MIS-C [14]; we have also described a similar case before [29]. In this analysis, we extracted the cases with a description of apex rounding or other segmental contractility abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a strong inflammatory reaction can be seen as a sufficient trigger for the occurrence of TTS. Belhadjer mentioned an echocardiographic image resembling TTS in a patient with acute heart failure in the course of MIS-C [14]; we have also described a similar case before [29]. In this analysis, we extracted the cases with a description of apex rounding or other segmental contractility abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…The acute and reversible nature of the heart failure in the course of MIS-C might resemble the picture of takotsubo syndrome (TTS) [27,28]. We have described such a case of TTS in the course of MIS-C before [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews on the manifestations of cardiac involvement in patients with MIS‐C revealed a high rate of coronary artery dilatation or aneurysms ranging from 14% to 48% 40–42 . While no specific risk factors or demographic features for early identification of those at risk were previously reported, a recent report by Ludwikowska et al 43 . stated that younger children are more likely to develop coronary artery abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In MIS-C, cardiac involvement is frequent, as it has been estimated that approximately up to 80% of affected children develop manifestations from the cardiovascular system [11][12][13]. These manifestations include ventricular dysfunction, valvular dysfunction, pericardial effusion, arrhythmias, conduction disorders, Coronary Artery Abnormalities (CAA) and in severe cases acute heart failure and cardiogenic shock [5,11,[14][15][16]. From the above, the most common cardiac finding in MIS-C, is Left Ventricular (LV) systolic myocardial dysfunction, which may range from subclinical myocardial injury to severe dysfunction [5,11,13,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…From the above, the most common cardiac finding in MIS-C, is Left Ventricular (LV) systolic myocardial dysfunction, which may range from subclinical myocardial injury to severe dysfunction [5,11,13,16,17]. Within days to weeks from the acute illness, the cardiac manifestations, that are described in this syndrome, usually resolve and conventional echocardiographic parameters like the LV Ejection Fraction (LVEF) return to normal, especially after the administration of effective treatment [14,18,19]. Nevertheless, it has been reported that despite preserved LVEF, cardiac strain abnormalities can be present in some patients, suggesting subclinical myocardial damage [4,14,19].…”
Section: Introductionmentioning
confidence: 99%